Onset age of mumps containing vaccine breakthrough cases with different vaccination doses and intervals - Haibo WANG; Guoyong SU; Xiaowei WANG; Yuanyong PAN; Chunfang HU (Zhongguo gonggong weisheng, 2023)
ObjectiveTo examine the onset age of mumps containing vaccine (MuCV) breakthrough cases with different vaccination doses and intervals for providing evidence to the formulation of immunization strategies. MethodsThe records of all mumps cases clinically diagnosed during 2019 – 2021 in Liuzhou city of Guangxi Zhuang Autonomous Region (Guangxi) were collected from China′s Infectious Disease Information System and the cases′ information on MuCV vaccination were retrieved from the Guangxi Immunization Planning Information Management System to screen out MuCV breakthrough cases. Age and MuCV vaccination characteristics of the breakthrough cases were analyzed. ResultsFor a total of 3 457 MuCV breakthrough cases occurred during the 3-year period in the city, the number of the cases with two MuCV doses was significantly lower than that of the cases with one dose (χ2 = 19.45, P < 0.05); the onset age of the breakthrough cases with two doses of MuCV were significantly higher than that of the cases with one dose (t = – 5.35, P < 0.05). For the breakthrough cases with two doses of MuCV, the onset age of the cases with a longer interval (≥4 years) between the two vaccinations was significantly higher than that of the cases with the interval less than 4 years (F = 12.98, P < 0.05). ConclusionThe two-dose MuCV vaccination with an interval of 4 years and longer could postpone the onset age of MuCV breakthrough incident and be more effective in controlling mumps incidence.